Forum Synthesis The contemporary debate on development sciences from the perspective of environmental sustainability, agroforestry systems and bioculturality: a synthesis - Lagos-Witte, Sonia; Díaz, Pablo Amilcar (Revista Perspectivas del Desarrollo, 2021)
The Forum: Contemporary Challenges of Development Sciences, organized in virtual mode by the Doctorate in Human Development Sciences of the National Autonomous University from May 10 to 17, 2021, generated a series of important discussions on Development Sciences that They have allowed the reflection of how, from the Academy, it can impact public policies towards sustainable development. Particularly on May 13, in the thematic axis "Environment and development" different topics were addressed around: "Current challenges for environmental sustainability and human development from the perspective of cultural and biological diversity, the recovery of agroforestry systems and food sovereignty"